Estoques de C e N em sistemas silvipastoris de alta e baixa diversidade arbórea: evidências de um experimento de campo de vinte e dois anos - Cá, Jorge (2021)
Integrated farming systems are one of the main strategies to reduce or compensate carbon emissions (C) of Brazilian agriculture, with simultaneous improvement in production efficiency. Among others, forestry systems have been promoted as sustainable models that combine livestock and forestry in the same area. The objective of this study was to evaluate the stocks of C and N and the natural abundance of 13C (δ13C) in the organic matter fractions of the soil, as well as the labile C of the soil, in long-term experiment (1997-2019) with silvipastoral systems with low and high tree diversity in the Atlantic Forest biome. Deformed and undeveloped soil samples were collected in transects perpendicular to the tree ranges every five meters (0, 5, 10 and 15 m away), at depths: 0.0-0.10, 0.10-0.30. 0.30-0.60, 0.60-1.0 m. We evaluated the burlap, root density, organic C contents and total N, the δ13C values of the fractions of particulate organic matter (POM) and associated minerals (MAOM) and the labile C of the soil, and later we calculated the stocks. The production of burlap was substantially higher in the high diversity system at all distances, except 5 m from the tree range. Contrary to the burlap, higher density of roots were observed in the largest distances of the trees (10 and 15 m). The high diversity arboreal forestry system increased the stocks of OCD in the surface layer (0.0-0.10 m, distances 0 and 10 m) and of C-MAOM in the surface (0.0-0.10 m, distance 10 m) and in the subsurface (0.10-0.30 m, distance 0 m). In addition, the total or associated N stocks of MAOM and POM in the 0.0-1.0 m layer were higher in the high diversity tree system. The increases were 37, 36 and 63%, respectively for total N, N-MAOM and N-POM. The less negative δ13C values, that is, the contribution of the graminea (C4) to the soil organic matter, in the soil surface layer (0.0-0.30 m) and in the depth 0.0-1.0 m in the distance 15 m in the high diversity system, in both fractions (MAOM and POM), highlights the role of grass-brachiaria in the incorporation of OCD. Overall, the high diversity arboreal forestry system has shown potential to store C in the upper layers of the soil and N of the soil up to 1 m deep. The silvipastoral system composed of grass-brachiaria consorting with leguminous tree species can be considered a viable strategy to increase the C and N stocks of the soil.